2013
DOI: 10.1152/ajpendo.00604.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide deficiency and diabetic renal remodeling: role of matrix metalloproteinase-9

Abstract: Kundu S, Pushpakumar SB, Tyagi A, Coley D, Sen U. Hydrogen sulfide deficiency and diabetic renal remodeling: role of matrix metalloproteinase-9. Am J Physiol Endocrinol Metab 304: E1365-E1378, 2013. First published April 30, 2013 doi:10.1152/ajpendo.00604.2012.-Matrix metalloproteinase-9 (MMP-9) causes adverse remodeling, whereas hydrogen sulfide (H2S) rescues organs in vascular diseases. The involvement of MMP-9 and H2S in diabetic renovascular remodeling is, however, not well characterized. We determined wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 46 publications
16
66
0
Order By: Relevance
“…This study showed upregulation of MMP-9 and downregulation of both CBS and CSE in renal tissue of diabetic (Akita, Ins2 Akita ) mice, whereas none of these changes occurred in double knockouts (Akita/MMP-9 −/− ). The relative H2S deficiency resulting from downregulation of its producing enzymes in turn is thought to upregulate N-methyl-d-aspartate receptor 1 and connexins 40 and 43 and thereby contribute to the adverse renal remodeling seen in diabetes [88]. In accordance, NaHS treatment has been reported to oppose the process of adverse renal remodeling in mice by adenosine monophosphate-activated protein kinase-dependent stimulation of autophagy and matrix metabolism [89].…”
Section: H2s In the Onset And Progression Of Renal Diseasementioning
confidence: 98%
“…This study showed upregulation of MMP-9 and downregulation of both CBS and CSE in renal tissue of diabetic (Akita, Ins2 Akita ) mice, whereas none of these changes occurred in double knockouts (Akita/MMP-9 −/− ). The relative H2S deficiency resulting from downregulation of its producing enzymes in turn is thought to upregulate N-methyl-d-aspartate receptor 1 and connexins 40 and 43 and thereby contribute to the adverse renal remodeling seen in diabetes [88]. In accordance, NaHS treatment has been reported to oppose the process of adverse renal remodeling in mice by adenosine monophosphate-activated protein kinase-dependent stimulation of autophagy and matrix metabolism [89].…”
Section: H2s In the Onset And Progression Of Renal Diseasementioning
confidence: 98%
“…Akita mice (82). In nonobese diabetic mice, another mouse model of type 1 diabetes, it was also shown that diabetic mice had lower H 2 S levels compared with nondiabetic mice (83).…”
Section: Hydrogen Sulfide and Microvascular Complications Of Diabetesmentioning
confidence: 98%
“…Renal protection via blood pressure reduction is also shown in angiotensin II-induced hypertension and proteinuria in rats (109). Other studies also suggest that H 2 S is a key modulator in renal remodeling and that its actions can be affected by the matrix metalloproteinase 9, which is shown to modulate CBS and CSE (82). In STZ-induced type 1 diabetic mice, the administration of H 2 S attenuated oxidative stress and inflammation, reduced mesangial cell proliferation, and inhibited the renin-angiotensin-aldosterone system (110).…”
Section: Nephropathymentioning
confidence: 98%
“…MMP-9 expression and activity are increased in the renal parenchyma in Akita mice with type 1 diabetes due to oxidative stress. Using MMP9 knockout mice in their studies, Kundu et al have shown that MMP-9 is involved in the reduced renal expression of CBS and CSE, leading to a decrease in H2S generation in diabetic mice (47). These investigators have proposed a link between MMP-9 activation, reduced H2S generation, and activation of N-methyl-d-aspartate receptor, leading to abnormal regulation of the gap junction proteins, connexins, that may be involved in renovascular remodeling (47).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Using MMP9 knockout mice in their studies, Kundu et al have shown that MMP-9 is involved in the reduced renal expression of CBS and CSE, leading to a decrease in H2S generation in diabetic mice (47). These investigators have proposed a link between MMP-9 activation, reduced H2S generation, and activation of N-methyl-d-aspartate receptor, leading to abnormal regulation of the gap junction proteins, connexins, that may be involved in renovascular remodeling (47). H2S inhibits diabetes-induced kidney injury by several other mechanisms, including inhibition of signaling mechanisms that govern protein synthesis.…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%